Dominican Republic Jobs Diagnostic - Winkler, Hernan; Montenegro, Miriam (Washington, DC: World Bank, 2021)
By many measures, the Dominican Republic experienced a stellar economic performance since the early 2000s. Upon closer inspection, however, progress has been slower than the aggregate indicators suggest. The fact that economic growth did not fully translate into higher job quality may help explain why the country’s poverty indicators only declined at the same average pace as other countries in Latin America and the Caribbean, even though its per capita gross domestic product (GDP) grew almost twice as fast as the regional average. This Jobs Diagnostic argues that the main labor market challenge facing the Dominican Republic is how to increase the quality of jobs in a sustained manner. Meeting this challenge is important both for achieving greater poverty reduction and shared prosperity in the medium term, as well as for rendering jobs less vulnerable to the risks posed by longer-term automation and globalization trends. This report presents new findings on the main bottlenecks that are hindering the creation of better jobs in the Dominican Republic and outlines the elements of a jobs strategy that can help remove them.